Pemberdayaan Kader Posyandu Melalui Seminar Pemanfaatan Teknologi untuk Pengembangan Media Promosi dengan Canva di Pondok Petir Kota Depok - Rinda Hesti Kusumaningtyas; Muhammad Fata Rayyan Ghafur; Reva Farell Putra; Raden Ayu Aninda; Muhammad Ilham Al Karim; Nisa Aulia Maharani (Lembaga Pengembangan Kinerja Dosen, 2026)
Empowering Posyandu cadresis one of the important strategies in improving the effectiveness of community-based health promotion,especially in the digital era. However, the limited skills of cadres in utilizing digital visual media are still anobstacle in creating interesting and communicative health information. This community service activity aims to improve the knowledge and skills of Posyandu cadres in Pondok Petir Village, Depok City, through seminars and training on the use of the Canva application as a medium for developing health promotion. The activity was conducted offline through lectures, discussions, and hands-on practice with intensive guidance. There were 25 participants, consisting of cadres and members of the local PKK. The results of the activity showed that most participants were able to understand and apply Canva's features to create health promotion media such as Posyandu schedule posters, immunization materials, and nutrition education. The enthusiasm of the participants during the practice sessions and their ability to produce informative and attractive visual designs demonstrated the success of this activity. Thus, Canva training has proven effective as a means of empowering Posyandu cadres in improving the quality of health communication and supporting the optimization of Posyandu services.